John Law, banker and economist - GAMBINO, A. (PSL Quarterly Review, 2014)
The article provides a critical re-examination of John Law’s activities and ideas, in light of a number of attempts that have been made, especially on the Continent, during the last thirty years, sometimes in apologetic vein, to rehabilitate the economist. The author examines the limitations of Law’s contribution to economic doctrine, and concludes that he does not deserve the reputation for originality and fertility which he has often enjoyed. Law’s conceptions were marred by an elementary and fundamental error: the failure to understand the connection between satisfying an additional demand for money and diminishing its value. No less serious were, as the author emphasises, Law’s mistaken notions concerning the limits to the expansion of bank credit. Even if it is possible to find in Law’s conception of the “power” of money something more than the mere naive identification of money with wealth, it would be an exaggeration to credit him with the far more sophisticated, but also more sober notions that in our generation have come to be associated with Keynes. JEL: B31, E41